PROSPEK PENGEMBANGAN MENDONG BAGI KABUPATEN SLEMAN - Purwanto, Sugeng; Handayani, Sugiharti Mulya (Universitas Sebelas Maret, 2006)
Mendong is a product of agriculture as material to make plait handicarf. Mendong is specific comodity because it's not producted in everywhere. Mendong was producted only in spesific region and one of them is Sleman. Mendong production of Sleman region have the best quality from other in Indonesia. In Sleman region, mendong just producted 0,68% from rice field that have good potency for mendong farm